Understanding the Path Toward Financial Well-Being: Evidence From India - Sehrawat, Kanchan; Vij, Madhu; Talan, Gaurav (Frontiers in Psychology, 2021)
Many countries are taking steps to establish national strategies to improve the financial wellbeing of their people. However, financial wellbeing as a term is still at infancy stage with a handful of model developed in the context of developed countries. Thus, there is a need to understand financial wellbeing from a multi-disciplinary and multi-dimensional approach to draft and implement efficient strategies especially in the context of developing countries like India. In our paper we have employed path-analysis to identify the specific constituents of financial literacy, financial behaviour, and personality traits that affect an individual’s financial wellbeing (perceived and objective) in Indian context. Survey responses of 349 respondents are analysed to empirically validate the proposed relationships using partial least squares structural equation modelling (PLS-SEM) approach. Our analysis mostly provides support to existing literature and challenges some. The findings provide support to thirteen out of seventeen tested effects with eight hypotheses. The understanding of pathways that lead to the increased financial wellbeing of individuals have the potential to facilitate effective policymaking and curriculum designing to support individuals’ efforts towards higher financial wellbeing and responsible financial behaviours.